Coal utilization eco-paradigm towards an integrated energy system. (October 2017) - Xu, Jiuping; Dai, Jingqi; Xie, Heping; Lv, Chengwei
Abstract: Over the past few centuries, coal has played a significant role in providing the world with the energy needed to encourage development. Since the 1990s, however, the environmental influence of the use of coal on the greenhouse effect and climate change has become a major concern to governments around the world. To explore the historic evolution of and the future trends in coal utilization, an optimized data analysis system (ODAS) based on research and environmental policies is proposed in this paper. Paradigm theory is adopted to explain the technological changes and the vital ecological coal utilization phases, and an imaginary no-coal-on-the-ground integrated energy system is introduced as a future coal utilization development. The advantages of ecological coal utilization are examined to develop possible policies and directions to assist the coal industry move towards green, clean production. Examining coal utilization using the ecological paradigm allows for an accurate view of coal future, with integrated energy systems expected to be a significant new trend. Abstract : Highlights: An optimized data analysis system is proposed for trajectory of coal utilization. Paradigm theory is used to analyze coal utilization development trends. The relationship between the technology, science and policy is considered. An integrated energy system is proposed based previous paradigm research. Timeline highlights some notable technology and policy's interactive developments.